Protein C, protein S, antithrombin III, and hyperfibrinogenemia in deep vein thrombosis (DVT) among patients who underwent high risk orthopaedic surgery (Medical Journal of Indonesia, 2004)
Post operative DVTÂ is believed to be rare in Indonesia, and so is trombophilia. It is necessary to know the incidence of postoperative DVT in Indonesia and thrombophlia profile (protein C, S, AT III deficiency and hyperfibrinogenemia) in DVT and non DVT patient who underwent orthopedic surgery involving the hip and knee (high risk surgery). A cross sectional study was conducted in 20 patients who underwent surgery involving the hip (total hip replacementÂ and fixation of proximal femoral fracture) and knee (total knee replacement and fixation of distal femoral fracture). Protein C, protein S, antithrombin III, and fibrinogen were examined in day 5 post operative, as well as with compression/Doppler USG between day 10 to 21 post operative, and confirmed by venography if USG findings was positive. Post operative DVT were found in 5 of 20 patients (25%). Deficiency of protein C (P= 0.46) protein S (P= 0.81), antithrombin III (P= 0.46), and hyperfibrinogenemia (P= 0.0547) did not correlate to post operative DVT. However, hyperfibrinogenemia was found to be a risk factor to post operative DVT (attributable risk= 1). Other confounding factor such as diabetes mellitus (P= 1.0), obesity (P= 0.28), hypertention (P= 1.0), hypertrigliseridemia, and hypercholesterolemia did not correlate to post operative DVT. The study suggested the existence of postoperative DVT cases in Indonesia. Hyperfibrinogenemia is a risk factor to promote post operative DVT. Deep vein thrombosis did not correlate to protein S, protein C, and antithrombin III deficiency. (Med J Indones 2004; 13: 24-30) Keywords: Thrombophilia, hip, knee, venography